Daniel Albright and Panaestheticism: The Counterpointed, the CounterTextual, and the Contrapuntal in Olivier Messiaen and T. S. Eliot. Issue 2 (August 2017) - Frendo, Maria
Abstract : This article looks at Daniel Albright's ideas on the integration, or otherwise, of the arts, specifically as presented in his book Panaesthetics (2014). Articulating a response to Jean-Luc Nancy's resonant question in The Muses, 'Why are there several arts and not just one?', Albright questions whether it is actually possible speak about 'unity' across the arts or whether 'diversity' remains what defines them. With that in view, the article looks at Olivier Messiaen's Harawi and T. S. Eliot's Four Quartets to discuss the countertextual and the contrapuntal, and how the poetic can there be observed in the musical and vice versa. In doing so, it also offers reflections on some implications for critical practice.